Sexual and bowel function in women with obstetric anal sphincter injuries after perineoplasty and sphincterorrhaphy - Imantika, Efriyan; Praharsini, Raden K.; Sasotya, Raden MS.; Ahmad, Eppy D.; Arev, Muhammad R.; Rinaldi, Andi; Prasetya, Aria (Narra J, 2026)
Obstetric anal sphincter injury (OASIS) may lead to persistent sexual and bowel dysfunction, even after surgical repair. Evidence on the functional outcomes after sphincterorrhaphy and perineoplasty remains limited, particularly in Indonesia. The aim of this study was to analyze the associations of perineal muscle strength and anal sphincter tone with sexual and bowel function in women with OASIS after sphincterorrhaphy and perineoplasty. This cross-sectional study was conducted at Hasan Sadikin Hospital, Bandung, Indonesia. Women with anal incontinence secondary to OASIS or fecal incontinence secondary to rectovaginal fistula who had undergone sphincterorrhaphy and perineoplasty were evaluated at three months after surgery. Vaginal tone and anal tone were assessed using perineometry and anometry, respectively. Sexual and bowel function were measured using the Female Sexual Function Index (FSFI) and Fecal Incontinence and Constipation Questionnaire (FICQ). Correlations were analyzed using Pearson’s correlation test. Maternal age was significantly associated with vaginal tone, with a moderate negative correlation (r=-0.318; p=0.021). Both vaginal tone and anal tone were positively associated with sexual function, with weak but significant correlations with FSFI score (r=0.30; p=0.042 and r=0.30; p=0.036, respectively). In contrast, maternal age, fetal birth weight, vaginal tone, and anal tone were not significantly associated with bowel function as measured by FICQ score. In conclusion, among women with OASIS who underwent sphincterorrhaphy and perineoplasty, vaginal and anal tones were significantly associated with sexual function at three months after surgery, suggesting that pelvic floor recovery may contribute to better postoperative sexual function.